Swot Analysis Of Marketing System Soy Milk In Sunggal Deli Serdang - Ocdy Amelia; Sulardi; Hardiansyah Putra; Muhammad Bahij Albaqy (International Journal of Management, Economic and Accounting, 2024)
Soy milk is a beverage product made from soybeans with the aim of increasing protein consumption. Soy milk itself has been widely known as an alternative milk to replace cow's milk for people who are allergic and do not like cow's milk or for those who cannot afford the relatively expensive price of cow's milk. The process of processing soybeans into good soy milk can create added value and also the utility value of the product so that it can increase the development of the current soy milk business. The partner in this activity is the soy milk business. In this home industry, the marketing management carried out is limited to products entrusted by street vendors, stalls and shops located near the production site. The lack of marketing management certainly causes the marketing area of the product to be less extensive. Therefore, a broader marketing management is needed.